Hold tight - Coben, Harlan (New York : Dutton, 2008)
Just how far parents will go to protect their kids? When their son Adam is implicated in the death of his classmate, Tia and Mike Baye install a sophisticated spy program on Adam's computer, and within days are jolted by a message from an unknown correspondent.
Keywords: Missing persons -- Fiction; Suicide -- Fiction; Thrillers (Fiction)